Caracterización de los actores de la cadena de la salsa en Cali - Ortega Cubillos, Solanlly (Universidad de San Buenaventura - Cali, 2018)
This written refers to the role play of the salsa actors in Cali, due to throough the time, it becomes in a significative industry for the city. Salsa has generated different passions which form a cultural heritage of it. This musical genre since beginnings starts to generate an important phenomena for the development of the culture around the world, the same situation happened here in Cali city where never mind social classes or kind of generations, Salsa rhythm but also “cholao, champus, lulada” belongs to caleños identity. Therefore and looking at the needed of Salsa’s sector this project looks for the characterization of the actors of salsa’s chain as a method of identification of the main people who give and makes of this sector a recognized style inside and outside of the country. Salsa has inspirated different boundaries such as: craftmen, workers, factories, Businessmen, technicians, salesclerks, manufacturers, composers, orchestras, record studios, managers, short films, numerous artistic creations which not only have a scenic display- bodily listed in an exhaustible human resourcbut also a human resource which influences in the economic growth of the city. Cali day by day reaffirms the feeling of belonging to the Salsa.